1985
DOI: 10.1128/aem.49.5.1295-1303.1985
|View full text |Cite
|
Sign up to set email alerts
|

Application of DNA-DNA colony hybridization to the detection of catabolic genotypes in environmental samples

Abstract: The application of preexisting DNA hybridization techniques was investigated for potential in determining populations of specific gene sequences in environmental samples. Cross-hybridizations among two degradative plasmids, TOL and NAH, and two cloning vehicles, pLAFR1 and RSF1010, were determined. The detection limits for the TOL plasmid against a nonhomologous plasmid-bearing bacterial background was ascertained. The colony hybridization technique allowed detection of one colony containing TOL plasmid among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(51 citation statements)
references
References 26 publications
0
49
0
2
Order By: Relevance
“…However, there have been few attempts to apply molecular approaches to ecological studies of chitinolytic bacteria in the marine environment, using, for example, nucleic acid probes for detection of bacteria possessing genes encoding for chitinase. Detection and quantitative determination of the presence (or absence) of a gene encoding a particular characteristic can be achieved with great speed and accuracy by nucleic acid hybridization, thus circumventing many limitations associated with conventional bacteriological methods [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few attempts to apply molecular approaches to ecological studies of chitinolytic bacteria in the marine environment, using, for example, nucleic acid probes for detection of bacteria possessing genes encoding for chitinase. Detection and quantitative determination of the presence (or absence) of a gene encoding a particular characteristic can be achieved with great speed and accuracy by nucleic acid hybridization, thus circumventing many limitations associated with conventional bacteriological methods [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using colony hybridization and hybridization to enrichment cultures have shown a correlation between a catabolic activity measurement and/or a most-probable number (MPN) enumeration of a specific catabolic type and an estimate of the microbial population density possessing the trait using a nucleic acid probe. The utility of DNA-targeted methods for monitoring bioremediation was first widely recognized in a report of pond sediment microcosms spiked with synthetic oil and analysed by colony hybridization (Sayler et al 1985). Exposure to synthetic oil increased the percentage of the total CFU that hybridized to the catabolic plasmids TOL and NAH7 up to 10-fold and > 3%fold, respectively, compared to nonspiked control microcosms.…”
Section: Dnata Rgeted Probesmentioning
confidence: 99%
“…Since the introduced bacteria often survive at a low population density, close to, or even below the detection level, our insight in the ecology of rhizobia is still incomplete. The same holds for plant pathogens [18][19][20], human and animal pathogens [21][22][23][24][25][26], and microbes involved in the degradation of xenobiotics [27][28][29]. 187…”
Section: Why Monitoring Microbes In the Environment?mentioning
confidence: 99%
“…DNA probes used in environmental studies may consist of relatively long cloned fragments of plasmids (e.g. [20,22,54,55]) or genes, such as cloned copper resistance genes [19,56], enterotoxin genes [57,58], and genes involved in the degradation of xenobiotics [29,[59][60][61][62]. Alternatively, the probes may consist of short (usual 20-30) nucleic acid sequences defined as oligonucleotide probes.…”
Section: Application Of Nucleic Acid Probes In Natural Populationsmentioning
confidence: 99%